SEXUAL COHABITATION AND RISK OF PREECLAMPSIA - Márquez, Santiago (2015)
To determine if the number of sexual intercourses with free exposure of the female genital tracto sperm before conception is associated with an in creased risk of developing preeclampsia during the sequent pregnancy. METHODOS: Case-control study at Hospital General Nacional Arzobispo Loayza. We studied 85 pregnant women with preeclampsia and 85 pregnant women without preeclompsia. Information was collected by patient interview. Data were analyzed with SPSS for MS Windows Release 6,1 and EPIINFO 6. RESULTS: Risk of preeclampsia increased 23 fold in pregnant women who had fewer than 6 sexual intercourses without barrier methods (exposures); risk was low with fewer than 6.3 exposures (p < 0, 0001). Risk of preeclampsia increased 3 fold in patients who had fewer than 18 months of sexual cohabitation (p = 0, 0024 7). Exposures and risk of severe preeclampsia were inversely related. CONCLUTION: Birth control methods that prevent exposure of the female genital tract to paternal antigens present in the sperm and short duration of sexual cohabitation before conception could be risk factors for development and severity of preeclampsia during the subsequent pregnancy.